Peningkatan Kompetensi Guru Bahasa Arab melalui Gamifikasi berbasis Educaplay di MTs. Al-Ajhariyyah Cibitung Bekasi - Masyitoh, Siti; Haniefa, Rifda; Mutmainah, Mia; Marzuq, Ahmad; Bachri, Arzu Putera; Ulya, Ayu Deena; Hakim, Lukman (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
Improving the quality of Arabic language learning in Islamic schools (madrasas) is an urgent need to improve students' understanding and language skills. One of the challenges faced by teachers is the limited mastery of innovative learning methods that can increase student learning motivation. Educaplay-based gamification offers an interactive approach that makes learning more interesting and effective. This activity aims to improve the competence of Arabic language teachers at MTs. Al-Ajhariyyah Cibitung Bekasi in designing and implementing gamification-based learning using the Educaplay platform. The method used is direct service in the classroom with activities involving educational games, quizzes, and interactive exercises based on Educaplay. The conclusion shows that the Educaplay-based gamification method is an effective and engaging learning method that can be used by teachers at MTs Al-Ajhariyyah Cibitung Bekasi to support the teaching and learning process and increase student engagement and learning outcomes.